Breaking bad news: a descriptive study of physicians’ perspective of Sindh, Pakistan - Abbas, Syed Hamza; Abbas, Syed Qamar; Mubeen, Syed Muhammad; Mubashir, Syed Muhammad; Zaman, Aliya (Journal of the Pakistan Medical Association, 2023)
Objective: To assess the perception and attitude of physicians related to breaking bad news. Methods: The cross-sectional study was conducted at three teaching hospitals in Karachi and Mirpurkhas, Pakistan, from April 2019 to February 2020, after approval from Hamdard University, Karachi, and comprised physicians of either gender having direct patient contact. Data was collected using a questionnaire based on literature. The questionnaire was pilot-tested before distribution among the subjects. The responses were categorised with respect to age, gender and professional experience. Data was analysed using SPSS 25. Results: Of the 230 subjects, 119(51.7%) were females. The overall mean age was 34.5±8.8 years and mean professional experience was 9.1±8.2 years. Overall, 19(8.3%) subjects believed they had a very good ability to deliver bad news, while 26(11.3%) avoided telling the patient the truth about diagnosis, prognosis and treatment. Age had a significant association with correctly defining breaking bad news (p<0.05). Conclusion: The skill level related to breaking bad news was found to be deficient. Key Words: Breaking bad news, Communication, Pakistan.